Peran dan Potensi Digitalisasi Manajemen Zakat: Sebuah Systematic Literature Review - Makarim, Dina Fornia; Hamzah, Muhammad Zilal (ITB AAS INDONESIA Surakarta, 2024)
This research aims to identify the role and potential of digitizing zakat management using a systematic literature review (SLR) approach with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method in the process of filtering articles according to the research subject. The data source comes from articles published by journals indexed by Scopus which were collected using the Publish or Perish (PoP) program. From a total of 112 studies, 47 articles were obtained from 33 Scopus indexed journals that were relevant for analysis, published in 2014-2024. Selected articles were analyzed using the VOSviewer tool. The results of this research show that digitalization in zakat management has an important role in the collection and distribution of zakat. Technologies such as blockchain and the use of bitcoin currency also have the potential to increase the role of digitalization of zakat management in the future. This research can be used as a reference for further research regarding the digitalization of zakat.